EXPRESSION OF RECOMBINANT CD25 ANTIGEN IN E. COLI - Huyền, Lã Thị (Vietnam Journal of Biotechnology, 2011)
CD25, also called IL-2Ra (the alpha chain of IL-2 receptor) is displ^ed with an elevated level on the lymphocytic cell surface in blood cancer (Hogdkin’s lymphoma, chronic myelogenous leukemia, dendritic cell lymphoma and adult human T cell lymphoma) and on pathogenic T cells in autoimmune diseases and transplant patients). Especially, CD25 is also present as soluble forms at high levels in semm of blood cancer patients, providing a good marker for diagnosis. CD25 may be a prospective target to kill pathogenic cells. Our study aimed at mass production of recombinant CD25. Thus, the human gene coding for the extracellular domain of CD25 was amplified, cloned and sequenced. Vector pET-22b(+)/CD25 has been constmcted and expressed sucessfiilly the recombinant CD25 in E. coli strain BL21(DE3) under conditions inducing with 1 mM IPTG at 30°C in 5 hours when ODftoonm of culmre is 0,8. In order to obtain recombinant CD25 antigen we use Ni-resin purification system and the primary stmcture of recombiant protein was identified by mass spectometry technique to approve the result. Finally, by gene technology we received purification CD25 protein, which can be used for next experiments.